PENGARUH PROSES REKRUTMEN DAN PROSES SELEKSI TERHADAP KINERJA KARYAWAN DI MCDONALD’S CABANG HASYIM ASHARI PINANG - Reiyen Monica Octatrivioni; Shella Puspita Sari (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Employee performance is one of the main factors determining a company’s success, particularly in the fast-food industry, which demands speed, accuracy, and consistency in service quality. Improving employee performance is closely related to effective human resource management, especially through appropriate recruitment and selection processes. This study aims to analyze the effect of recruitment and selection on employee performance at McDonald’s Hasyim Ashari Branch, both partially and simultaneously. This study uses a quantitative method. The research population includes all employees of McDonald’s Hasyim Ashari Branch, with a sample of 61 respondents determined using a saturated sampling technique. Data were collected through questionnaires, while data analysis was conducted using validity tests, reliability tests, classical assumption tests, simple and multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). The results show that recruitment has a positive and significant effect on employee performance, with a significance value of 0.000 (p < 0.05). Selection also has a positive and significant effect on employee performance, with a significance value of 0.000 (p < 0.05). Simultaneously, recruitment and selection have a significant effect on employee performance, with a coefficient of determination (R²) of 0.716, indicating that 71.6% of the variation in employee performance is influenced by recruitment and selection, while the remaining percentage is influenced by other factors outside this study. The conclusion of this study indicates that recruitment and selection play an important role in improving employee performance. Therefore, the company is advised to continuously improve the quality of recruitment and selection processes in an objective, transparent, and competency-based manner. Future research is expected to examine other variables that may influence employee performance in order to obtain more comprehensive results.